2003
DOI: 10.1046/j.1440-1614.2003.01174.x
|View full text |Cite
|
Sign up to set email alerts
|

A Memory Clinic at a Geriatric Hospital: A Report on 577 Patients Assessed with the CAMDEX Over 9 Years

Abstract: Patient demographics and diagnoses were similar to those found in other clinics. Most people who attended the memory clinic had significant cognitive or psychiatric disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
28
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 17 publications
7
28
1
Order By: Relevance
“…The ability of the IQCODE to discriminate AD is in line with previous studies [12,22,24] . The IQCODE was not able to discriminate MCI, which is in contrast to the findings of Isella et al [26] and Ehrensperger et al [25] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The ability of the IQCODE to discriminate AD is in line with previous studies [12,22,24] . The IQCODE was not able to discriminate MCI, which is in contrast to the findings of Isella et al [26] and Ehrensperger et al [25] .…”
Section: Discussionsupporting
confidence: 91%
“…Despite this widespread research in community samples, only a limited number of studies have investigated the use of the IQCODE in a memory clinic population [20][21][22][23][24] . In this setting, the IQCODE also seems to be able to differentiate between dementia patients and elderly individuals without cognitive deficits.…”
mentioning
confidence: 99%
“…One study by Nygaard et al [32] reported that carer information as measured by the IQCODE was influenced by the carer's burden of care. A similar result was reported from an Australian study [34]. However, in an earlier study from the same Australian group, the carer's burden did not influence the carer's information about the patient's cognitive decline [35].…”
Section: Introductionsupporting
confidence: 82%
“…Most do not provide details about the proportion of rural vs. urban patients but appear to be serving mainly urban patients. Of the 577 patients seen in an Australian memory clinic over a 9-year period (Stratford et al, 2003), the mean age was 72.9 years, identical to the overall mean age of patients seen in our clinic. English as a first language was spoken by 73% of patients and an interpreter used for 8% of assessments, compared to 94% and 5% of the current clinic population, respectively.…”
Section: Evaluation Of Clinic and Follow-up Interventionssupporting
confidence: 64%
“…Neuroradiological assessment was provided by most clinics (CT = 93%, MRI = 71%) (Lindesay et al, 2002). A well established clinic in Australia (Ames, Flicker, & Helme, 1992;Stratford et al, 2003) operates a half-day per week, seeing two new patients weekly. Assessments are conducted over two visits a few weeks apart, with a family conference at the end of the second visit.…”
Section: Memory Clinic Design and Operationsmentioning
confidence: 99%